2015
DOI: 10.1016/j.scr.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterisation of neuromuscular junctions between hiPSC derived motoneurons and myotubes

Abstract: Striated skeletal muscle cells from humans represent a valuable source for in vitro studies of the motoric system as well as for pathophysiological investigations in the clinical settings. Myoblasts can readily be grown from human muscle tissue. However, if muscle tissue is unavailable, myogenic cells can be generated from human induced pluripotent stem cells (hiPSCs) preferably without genetic engineering. Our study aimed to optimize the generation of hiPSCs derived myogenic cells by employing selection of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 34 publications
0
83
0
1
Order By: Relevance
“…For this reason, there have been several efforts to establish a co-culture system of PSC-derived myogenic cells with rat embryonic spine or with PSCderived motoneurons. This system improved the maturation of PSC-derived myofibers, as evidenced by AchR clustering and electrophysiological recordings (Demestre et al, 2015;Puttonen et al, 2015;Rohwedel et al, 1998b); however, electrophysiological analysis suggested immaturity of neuromuscular junction activity (Puttonen et al, 2015;Vyskočil and Vrbová, 1993).…”
Section: Excitation-contraction Couplingmentioning
confidence: 98%
See 2 more Smart Citations
“…For this reason, there have been several efforts to establish a co-culture system of PSC-derived myogenic cells with rat embryonic spine or with PSCderived motoneurons. This system improved the maturation of PSC-derived myofibers, as evidenced by AchR clustering and electrophysiological recordings (Demestre et al, 2015;Puttonen et al, 2015;Rohwedel et al, 1998b); however, electrophysiological analysis suggested immaturity of neuromuscular junction activity (Puttonen et al, 2015;Vyskočil and Vrbová, 1993).…”
Section: Excitation-contraction Couplingmentioning
confidence: 98%
“…Notably, PDGFRα + /VEGFR2 − cells isolated from differentiating PSC cultures have been proposed to correspond to putative paraxial mesoderm progenitors, including premyogenic cells (Darabi et al, 2012(Darabi et al, , 2008Sakurai et al, 2009Sakurai et al, , 2012. Myogenic progenitors have also been isolated from mouse or human PSC cultures using CD106 (VCAM1, SM/C2.6) (Chang et al, 2009;Mizuno et al, 2010), CD34 (Demestre et al, 2015), CD56 (NCAM1) (Young et al, 2016), CD56 and CD73 (Barberi et al, 2007), CD82 (Uezumi et al, 2016), CXCR4 (CD184) and c-Met (Borchin et al, 2013). However, the usefulness of these markers is limited by their overall poor lineage specificity.…”
Section: Box 1 Tools For Characterizing Psc-derived Myogenic Progenimentioning
confidence: 99%
See 1 more Smart Citation
“…Human iPSC-derived motor neurons have been cocultured with skeletal muscle from various human and nonhuman sources as a means to study neuromuscular junction formation and function [Demestre et al, 2015;Puttonen et al, 2015;Santhanam et al, 2018]. Such models can be used to test the efficacy of pharmacological agents as well as to model synaptic breakdown in cases of neuromuscular disorders, such as spinal muscular atrophy [Yoshida et al, 2015].…”
Section: Complexitymentioning
confidence: 99%
“…Interestingly, these authors were able to detect expression of the secondary myogenesis marker Nfix [69], transition from the embryonic slow myosin to the perinatal isoform, and an overall high myofibril organization. Multiple groups have interpreted the incomplete electrophysiological maturation as a consequence of the lack of innervation and establishment of co-culture protocols could represent an alternative for overcoming this issue [155]. Interestingly, lack of maturation seems to be a less relevant issue for cell therapy applications.…”
Section: Current Issues and Future Applications Of Pluripotent Stementioning
confidence: 99%